2020
DOI: 10.1038/s41467-020-17971-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for the detection of COVID-19 pneumonia on chest CT using multinational datasets

Abstract: Chest CT is emerging as a valuable diagnostic tool for clinical management of COVID-19 associated lung disease. Artificial intelligence (AI) has the potential to aid in rapid evaluation of CT scans for differentiation of COVID-19 findings from other clinical entities. Here we show that a series of deep learning algorithms, trained in a diverse multinational cohort of 1280 patients to localize parietal pleura/lung parenchyma followed by classification of COVID-19 pneumonia, can achieve up to 90.8% accuracy, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
371
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(407 citation statements)
references
References 25 publications
(36 reference statements)
1
371
1
4
Order By: Relevance
“…The SARS-CoV-2 (COVID-19) outbreak at the end of 2019, which results from contracting an extremely contagious beta-coronavirus, has spread worldwide and is responsible for the latest pandemic in human history. Prior studies report frequent use of chest computed tomography (CT) in patients suspicious of pneumonia, including COVID-19 [ 1 , 4 , 10 , 14 , 16 ]. Chest CT is often recommended to assess disease severity and monitor progression in patients with moderate to severe pneumonia as well as to assess suspected complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 (COVID-19) outbreak at the end of 2019, which results from contracting an extremely contagious beta-coronavirus, has spread worldwide and is responsible for the latest pandemic in human history. Prior studies report frequent use of chest computed tomography (CT) in patients suspicious of pneumonia, including COVID-19 [ 1 , 4 , 10 , 14 , 16 ]. Chest CT is often recommended to assess disease severity and monitor progression in patients with moderate to severe pneumonia as well as to assess suspected complications.…”
Section: Introductionmentioning
confidence: 99%
“…Chest CT is often recommended to assess disease severity and monitor progression in patients with moderate to severe pneumonia as well as to assess suspected complications. In sites with limited availability of reverse transcription polymerase chain reaction (RT-PCR) and high disease prevalence, chest CT is also used in diagnosis for patients with suspected COVID-19 [ 1 , 4 , 10 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…An AI based CT diagnosis, which demonstrates an accuracy level 95%, proves to have a promising role in the diagnosis of the disease. On a gross spectrum the accuracy was 90.8%, which is superior to RT-PCR with a sensitivity of 60-70% [22]. This study highlights the need for a combination of RT-PCR and CT scans in the detection of COVID19.…”
Section: Rt-pcr and Artificial Intelligence Combinationmentioning
confidence: 72%
“…Owing to its increased availability, RT-PCR is the gold standard in diagnosis. CT scans have diagnosed patients in RT-PCR negative cases [22]. An AI based CT diagnosis, which demonstrates an accuracy level 95%, proves to have a promising role in the diagnosis of the disease.…”
Section: Rt-pcr and Artificial Intelligence Combinationmentioning
confidence: 99%
“…Emerging artificial intelligence techniques useful for distinguishing between these observations may reinforce support in the direction of practice of CT scan in the diagnostic settings ( Mei et al, 2020 ). A recent report developed AI algorithm and evaluated for the diagnosis of SARS-CoV-2 using chest CT scans applicable for data from a worldwide and from all sort of institution datasets ( Harmon et al, 2020 ). This study showed the possibility of preparing robust models that can achieve accuracy up to 90% in diverse test populations, with retaining high specificity in other related pneumonia infections, and thus validated sufficient predictability to unnoticed patients.…”
Section: Diagnostic Technologies For Sars-cov-2mentioning
confidence: 99%